The Evaluation Study of Implementation National Standard Library for University (SNPPT) in Universitas Pembangunan Nasional “Veteran” East Java - A. Prathama; A. Kriswibowo (Future Science)
College libraries play an important role in the Tri Dharma of Higher Education action. General education, education up to community service. UPN